Precise measurement of the top-quark mass from lepton+jets events at D0 - Abazov, V. M. (2011)
We report a measurement of the mass of the top quark in lepton+jets final states of pp̄→tt̄ data corresponding to 2.6fb-1 of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider. A matrix-element method is developed that combines an in situ jet energy calibration with our standard jet energy scale derived from studies of γ+jet and dijet events. We then implement a flavor-dependent jet-response correction through a novel approach. This method is used to measure a top-quark mass of mt=176.01±1.64GeV. Combining this result with our previous result obtained on an independent data set, we measure a top-quark mass of mt=174.94±1.49GeV for a total integrated luminosity of 3.6fb-1. © 2011 American Physical Society.